Surface study of graphene ink for fine solid lines printed on BOPP Substrate in micro-flexographic printing using XPS analysis technique - Hassan, S.; Yusof, M. S.; Embong, Z; Ding, S.; Maksud, M. I. (IOP Publishing, 2018)
Micro-flexographic printing is a combination of flexography and micro-contact printing technique. It is a new printing method for fine solid lines printing purpose. Graphene material has been used as depositing agent or printing ink in other printing technique like inkjet printing. This graphene ink is printed on biaxially oriented polypropylene (BOPP) by using Micro-flexographic printing technique. The choose of graphene as a printing ink is due to its wide application in producing electronic and micro-electronic devices such as Radio-frequency identification (RFID) and printed circuit board. The graphene printed on the surface of BOPP substrate was analyzed using X-Ray Photoelectron Spectroscopy (XPS). The positions for each synthetic component in the narrow scan are referred to the electron binding energy (eV). This research is focused on two narrow scan regions which are C 1s and O 1s. Further discussion of the narrow scan spectrum will be explained in detail. From the narrow scan analysis, it is proposed that from the surface adhesive properties of graphene, it is suitable as an alternative printing ink medium for Micro-flexographic printing technique in printing multiple fine solid lines at micro to nano scale feature